Unveiling triterpenoid superiority in a newly developed Ganoderma lucidum variety through untargeted metabolomics approach - Pan, Zhibin; Lin, Junhan; Luo, Gelian; Cheng, Weiqing; Li, Ye; Wu, Changhui (Frontiers in Nutrition, 2025)
The fruiting bodies of Ganoderma lucidum are renowned for their therapeutic properties, primarily due to their triterpenoid content. Variability in G. lucidum strains may influence the composition and abundance of triterpenoids. In this study, we explored the triterpenoid superiority in a newly developed G. lucidum strain (GL_V2) obtained through mutation breeding, and compared it to a widely cultivated strain (GL_V1). GL_V2 exhibited a 1.4-fold increase in total triterpenoid content and higher DPPH radical scavenging activity compared to GL_V1, while polysaccharide levels remained consistent. Using UPLC-Q-Orbitrap-MS and chemometric analyses, we identified 589 metabolites, including 86 triterpenoids. Multivariate statistical analyses revealed clear differences in overall metabolite profiles and triterpenoid compositions between the two strains. OPLS-DA identified 56 triterpenoids as key distinguishing markers with VIP values above 1.0. Notably, GL_V2 exhibited increased levels of seven ganoderic acids, two ganoderiols, three ganolucidic acids, and two ganosporelactones, while GL_V1 showed higher concentrations of six lucidenic acids. These results highlight the superior triterpenoid composition of GL_V2 and its potential for developing more potent G. lucidum-derived products. This study offers valuable insights into varietal differences in triterpenoid profiles and their implications for the cultivation and therapeutic use of G. lucidum. Additionally, the findings of this study suggest that GL_V2 holds significant potential for the development of more effective nutraceutical and pharmaceutical products derived from G. lucidum.